CuO promoted Mn2O3-based materials for solid fuel combustion with inherent CO2 capture1. Issue 19 (21st May 2015) - Hosseini, D.; Imtiaz, Q.; Abdala, P. M.; Yoon, S.; Kierzkowska, A. M.; Weidenkaff, A.; Müller, C. R.
<x xml:space="preserve">Abstract</x> A novel bimetallic Cu–Mn oxygen carrier for Chemical-Looping with Oxygen Uncoupling (CLOU) based CO2 capture.